2010
DOI: 10.1163/138855409x12571623969727
|View full text |Cite
|
Sign up to set email alerts
|

Schistonchus hirtus n. sp. (Nematoda: Aphelenchoididae), an associate of Ficus hirta in China

Abstract: A nematode recovered from syconia of Ficus hirta from Guangzhou, P. R. China, during a survey of nematode biodiversity from 2007 to 2009, is described herein as Schistonchus hirtus n. sp. and is differentiated by a combination of morphological characters, including excretory pore (EP) located near the metacorpus, a short post-uterine sac (PUS) (0.5 vulval body diam. (VBD) long), rose thorn-shaped spicules, amoeboid sperm, absence of gubernaculum, three pairs of subventral papillae on the male tail, host-Ficus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
(5 reference statements)
7
15
0
Order By: Relevance
“…Paraphyly of these genera was described in Zhao et al (2008), when fewer sequences were available. Paraphyly of Schistonchus has been confirmed by independent analyses including sequences of SSU from S. caprifici (De Luca et al, 2010;Zeng et al, 2010). The genus needs revision.…”
Section: Genetics Of Schistonchusmentioning
confidence: 83%
See 2 more Smart Citations
“…Paraphyly of these genera was described in Zhao et al (2008), when fewer sequences were available. Paraphyly of Schistonchus has been confirmed by independent analyses including sequences of SSU from S. caprifici (De Luca et al, 2010;Zeng et al, 2010). The genus needs revision.…”
Section: Genetics Of Schistonchusmentioning
confidence: 83%
“…Some species used in these figures are from previous sequencing projects (Ye et al, 2007a;Gulcu et al, 2008;Kanzaki et al, 2009;Zeng et al, 2010). Additional species were obtained from GenBank (associated accession number is listed in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…with other described species in Schistonchus is not well resolved, but probably represents another 'Schistonchu. 'i' lineage (Zeng et al, 2010). Davies et al (2013) inferred that S. baculum and S. guangzhouensis are putative sisters in a single clade based on phylogenetic analysis (Davies et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al (1973) reported a variety of different ne matode types associated with figs in tropical Africa, but provided few taxonomic details. Two nematode genera, Schistonchus Cobb, 1927(Fuchs, 1937) (Aphelenchoididae) and Parasitodiplogaster Poinar, 1979 (Diplogastridae), are well known from inside the sycones of Ficus species worldwide (Gasparrini, 1864;Poinar, 1979;Kumari & Reddy, 1984;Reddy & Rao, 1984;Poinar & Herre, 1991;Giblin-Davis et al, 1995, 2003, 2006Lloyd & Davies, 1997;DeCrappeo & Giblin-Davis, 2001;Anand, 2002;Zeng et al, 2007Zeng et al, , 2010Zeng et al, , 2011Zeng et al, , 2013aBartholomaeus et al, 2009Bartholomaeus et al, , 2012Davies et al, 2009Davies et al, , 2010Kanzaki et al, 2010Kanzaki et al, , 2012Kanzaki et al, , 2013Kanzaki et al, , 2014aWohr et al, 2014). Schistonchus is a polyphyletic plant-parasitic nematode grouping in the Aphelenchoididae that feeds and reproduces on the epidermis of florets inside the sycone and is an internal phoretic of its fig wasp pol linator host which transports it to the next suitable fig (Vovlas etal., 1992(Vovlas etal., , 1996Giblin-Davis etal., 1995;Cen ter et al, 1999;Davies et al, 2010).…”
mentioning
confidence: 99%